The causal structure of land finance, commercial housing, and social housing in China. Issue 2 (3rd April 2019) - Jin, Chenghua; Choi, Mack Joong
ABSTRACT: China has implemented the dual housing supply system consisting of commercial housing provided by the private sector and social housing provided by the public sector. Since commercial housing and social housing are mediated by the land finance of local governments, however, an increase in the supply of commercial housing contributes to the income of the land finance, which may, in turn, increase the public expenditure on the supply of social housing. Though the supply of commercial housing has increased and the size of the land finance has expanded in the process of rapid urbanization in China, however, statistics do not support that the supply of social housing has increased in proportion to the supply of commercial housing. The purpose of this paper is to empirically analyse the relationship among commercial housing supply, social housing supply, and the land finance in order to verify whether the two housing types are in the indirect, complementary relationship mediated by the land finance or in the direct, substitutive relationship. The cross-sectional data is used across 274 cities in China, based on the annual average values between 2009 and 2014 regarding each city's size of land finance and the amount of land supplied for construction purposes, which includes commercial housing and economic comfortable housing. By the path analysis results that commercial housing and ECH are not in the complementary relationship mediated by the land finance, but in the substitutive relationship as they have to compete each other to secure the limited land resources.